Immune-related adverse events with immune checkpoint blockade: a comprehensive review. (February 2016) - Michot, J.M.; Bigenwald, C.; Champiat, S.; Collins, M.; Carbonnel, F.; Postel-Vinay, S.; Berdelou, A.; Varga, A.; Bahleda, R.; Hollebecque, A.; Massard, C.; Fuerea, A.; et al.
Abstract: Cancer immunotherapy is coming of age; it has prompted a paradigm shift in oncology, in which therapeutic agents are used to target immune cells rather than cancer cells. The first generation of new immunotherapies corresponds to antagonistic antibodies that block specific immune checkpoint molecules cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), programmed cell death protein (PD-1) and its ligand PD-L1. Targeting these checkpoints in patients living with cancer had led to long-lasting tumour responses. By unbalancing the immune system, these new immunotherapies also generate dysimmune toxicities, called immune-related adverse events (IRAEs) that mainly involve the gut, skin, endocrine glands, liver, and lung but can potentially affect any tissue. In view of their undisputed clinical efficacy, anti-CTLA-4 and anti-PD-1 antibodies are entering in the routine oncological practice, and the number of patients exposed to these drugs will increase dramatically in the near future. Although steroids can be used to treat these IRAEs, the associated immunosuppression may compromise the antitumour response. Oncologists must be ready to detect and manage these new types of adverse events. This review focuses on the mechanisms of IRAE generation, putative relationship between dysimmune toxicity and antitumour efficacy, as a basis for management guidelines. Highlights: Programmed cell death protein-1 and cytotoxic T-lymphocyte-associated antigen-4 have roles in self-tolerance and various auto-immune conditions. Tumour neoantigens and normal tissue antigens could be cross-reactive. A correlation between dysimmune toxicity and antitumoural efficacy is emerging. Steroids must be used with caution in routine practice to treat dysimmune toxicity.